Sepsis-Induced Immunosuppression in Neonates - Hibbert, Julie E.; Currie, Andrew; Strunk, Tobias (Frontiers in Pediatrics, 2018)
Neonates, especially those born preterm, are at increased risk of sepsis and adverse long-term effects associated with infection-related inflammation. Distinct neonatal immune responses and dysregulated inflammation are central to this unique susceptibility. The traditional separation of sepsis into an initial hyper-inflammatory response followed by hypo-inflammation is being challenged. Emerging evidence suggests that hypo- and hyper-inflammation can occur during any phase of sepsis and that sepsis-immunosuppression is associated with increased mortality, morbidity and risk to subsequent infection. In adults, sepsis-immunosuppression is characterised by alterations of innate and adaptive immune responses, including, but not limited to, a prominent bias towards anti-inflammatory cytokine secretion, diminished antigen presentation to T cells, and reduced activation and proliferation of T cells. It is unclear if sepsis-immunosuppression also plays a role in the adverse outcomes associated with neonatal sepsis. This review will focus on exploring the evidence for key immunosuppression characteristics associated with sepsis severity and risk of increased susceptibility to subsequent nosocomial infections in neonates with sepsis.